2017
DOI: 10.1111/joic.12404
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of contrast‐induced acute kidney injury by early post‐procedural analysis of urinary biomarkers and intra‐renal Doppler flow indices in patients undergoing coronary angiography

Abstract: Joint assessment of early post-procedural urinary biomarkers and Doppler renovascular parameters aids early diagnosis of CI-AKI in patients undergoing coronary interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…In our study, SEN, SPE, and AUC were used for indicating the performance of uKIM-1 for CI-AKI prediction; all the studies showed that uKIM-1 was a good predictor. e AUC values were above 0.70 for all studies (in fact, two studies reported an AUC >0.90 (18,22)). Moreover, the pooled AUC (0.88, 95% CI 0.85-0.90) also indicates a considerable value in using uKIM-1 for the diagnosis of CI-AKI.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In our study, SEN, SPE, and AUC were used for indicating the performance of uKIM-1 for CI-AKI prediction; all the studies showed that uKIM-1 was a good predictor. e AUC values were above 0.70 for all studies (in fact, two studies reported an AUC >0.90 (18,22)). Moreover, the pooled AUC (0.88, 95% CI 0.85-0.90) also indicates a considerable value in using uKIM-1 for the diagnosis of CI-AKI.…”
Section: Discussionmentioning
confidence: 78%
“…All studies were single-center trials that had their findings published between 2013 and 2017. Of the included studies, 7 were published in English [ 8 – 10 , 17 19 , 22 ], and 2 were published in Chinese [ 20 , 21 ]. The 9 studies included a total of 946 adult patients from 5 countries who underwent PCI or GAC, and 144 were diagnosed as CI-AKI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phase has been defined “ subclinical AKI ” (Figure ). In the present issue of the Journal of Interventional Cardiology Wybraniec et al report the advantage of the combined assessment of urinary IL‐18 at 6 h and the renal resistive index at 1 h after CM exposure for the early diagnosis of CI‐AKI after coronary artery procedures . However, it is still unclear (i) whether one biomarker should be preferred to others in the setting of CI‐AKI; (ii) which is the best time‐window between CM exposure and assessment of AKI; and (iii) whether the assessment of these new biomarkers and/or non‐invasive indices might guide the therapeutic approaches and therefore improve the early and long‐term outcome.…”
Section: Ci‐aki Definitionmentioning
confidence: 97%
“…Many demographic, clinic, laboratory, and imaging method parameters were found related to CIN development. Very recently, pre-and post-CA/PCI procedural renal resistive index (RRI) obtained by renal Doppler ultrasonography (USG) were reported as significantly and independently related to CIN occurrence [3,4]. RRI is the most frequently used and acknowledged renal Doppler USG parameter, but it is affected by many demographic, clinic, and systemic parameters [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%